Annual Plan 2009-10 G.N. Statement Planning & Development Department Govt. of Jharkhand - Planning Commission (Planning Commission, 2009)
Draft annual plan (2009-10) proposed outlays, annual plan- 2009-10 proposed outlays (from state budget), annual plan- 2009-10- proposed outlays (from pse's), annual plan- 2009-10- proposed outlays (from local bodies), annual plan- 2009-10- proposed outlays (rural local bodies), annual plan- 2009-10- proposed outlays (urban local bodies), annual plan- 2009-10- proposed outlays (total of rural local bodies & urban local bodies), draft annual plan - 2009-10 proposed outlays (sci1emewise),
Planning & Development Department Govt. of Jharkhand